Essential Role of Interleukin-1 Signaling in Host Defenses Against Group B Streptococcus - Biondo, Carmelo (American Society of Microbiology, 2014)
Signal transduction via MyD88, an adaptor protein engaged by the Toll-like receptor (TLR) and interleukin-1 receptor (IL-1R) family receptors, has a crucial role in host defenses against group B streptococcus (GBS). To examine the contribution of IL-1R signaling to MyD88-dependent host defenses, we analyzed GBS infection in type I IL-1R (IL-1RI)-deficient mice. Most of these animals displayed clinical signs of sepsis and neurological disease and died after a challenge with a bacterial dose that did not cause illness or death in any of the wild-type animals. Moreover, bacterial numbers in the blood and brains of the immunodefective mice were considerably increased. The ability of blood leukocytes or bone marrow-derived macrophages to kill GBS in vitro was not affected by a lack of IL-1RI. However, it was found in a newly developed model of GBS-induced peritoneal inflammation that IL-1 signaling selectively promoted the production of the chemokines KC and MIP-1α and neutrophil recruitment. Moreover, the secretion of KC and MIP-1α, but not tumor necrosis factor alpha, by peritoneal macrophages stimulated with GBS was significantly decreased in the absence of IL-1RI. Accordingly, the number of neutrophils in the blood and the concentration of myeloperoxidase, a neutrophil marker, in infected organs were severely reduced in the immunodefective mice during GBS disease, concomitantly with a reduction in tissue KC and MIP-1α levels. In conclusion, IL-1RI plays a crucial role in host defenses against GBS by inducing the high-level production of chemokines and the subsequent recruitment of neutrophilic polymorphonuclear leukocytes to infection sites.